Cupping Therapy for Temporary Reduction of Blood Pressure in Hypertension Patients - Erwin Rachman, Mochammad; Nur Rachman, Aksa (Fakultas Kedokteran Universitas Muslim Indonesia, 2020)
Introduction: Hypertension is still a major problem in the field of health problems in general. One therapy to cure hypertension is cupping technique therapy. Objectives: To find a picture of a brief decrease in blood pressure in patients with hypertension using cupping therapy techniques. Methods: This study was a descriptive study using purposive sampling totaling 85 populations and 46 samples. Results: The results showed that the average systolic blood pressure before cupping was 164.78 mmHg decreased by 10.87 mmHg to 153.91 mmHg after cupping and the average diastolic blood pressure before cupping was 99.78 mmHg decreased by 4.13 mmHg to 95.65 mmHg. Conclusion: The results showed that cupping technique therapy can reduce blood pressure for a moment in hypertension sufferers.